HISTORY OF HOLOCENE SEDIMENTATION IN THE SOUTHERN KARA SEA - Levitan M.A.; Krupskaya V.V.; Sedykh E.M.; Bourtman M.V.; Demina L.L.; Chudetsky M.Yu. (My University, 2004)
Two bottom sediment cores (BP00-23/7 and BP00-7/6) recovered from the Yenisei transect in the southern Kara Sea are described. Data on their grain size composition, clay and heavy mineral assemblages, and distribution of a large group of chemical elements are presented. Radiocarbon dates based on AMS C-14 method suggest the Holocene age of sediments in the cores. Literature data on physical properties and foraminifers have also been analyzed. The facies affiliation of the lithostratigraphic subdivisions has been unraveled. History of the Yenisei River runoff in the Holocene has been reconstructed on the basis of different indicators.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен